Investigation of low velocity impact behaviors of honeycomb sandwich composites - Topkaya, Tolga; Solmaz, Murat Yavuz (Korean Soc Mechanical Engineers, 2018)
Honeycomb sandwich composites are used as significant structural members in advanced engineering applications. Thus, it is critical to determine how they behave under impact loading, in addition to other loads. In this study, low velocity impact loading behaviors of honeycomb sandwich composites were experimentally investigated. Almost all of the design parameters of honeycomb sandwich composites were investigated. The results indicated that the core thickness of honeycomb had no effect on the strength of the composite, and the parameter influencing the impact behavior of the specimen the most was the face sheet thickness. When the face sheet thickness of the specimen was increased, the most apparent strength increase was observed in the models using carbon fiber-reinforced composite face sheets. For all face sheet types subject to impact energy of 10 Joules, the upper face sheets of 0.5 mm-thick specimens were perforated.
Keywords: Honeycomb sandwich composites; Low velocity impact; CFRP